Real men don't talk? Relationships among depressiveness, loneliness, conformity to masculine norms, and male non-disclosure of mental distress - Anna J.M. Wagner; Doreen Reifegerste (Elsevier, 2024)
Men are a particularly challenging group when it comes to mental health communication. Non-disclosure of mental distress is quite common among men in general, and even more so among depressed men - despite its detrimental effects on health. Motivating men to share their mental distress with trusted social contacts serves as a vital first step in addressing and improving their mental health - both for those men who are affected by mental illness and those who are not. To overcome the barriers to communicating about mental distress, knowledge about the aspects associated with non-disclosure is indispensable. Bringing together assumptions from interpersonal communication and (mental) health communication literature, we propose a conceptual model of the relationships among depressiveness, loneliness, conformity to masculine norms, number of trusted social contacts, and non-disclosure of mental distress. To empirically test our model, we conducted a cross-sectional online survey with 1,400 men in Germany. Findings largely substantiate our model. They show that a higher depressiveness is positively associated with men's non-disclosure of mental distress - both directly and mediated through several other variables. Loneliness emerged as an important mediating factor, with a higher depressiveness being linked to higher loneliness, which increased the likelihood for men's non-disclosure. Depressiveness was also associated with a higher conformity to traditional masculine norms, again making non-disclosure of mental distress more probable.